PEMANFAATAN TEPUNG KELAPA DALAM PEMBUATAN MI KERING - Tarigan, Teddy Yohannes; Efendi, Raswen (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this research was to obtain the optimal formula of wheat flour and coconut flour on the dry noodle which meet the quality standart of dry noodle. The design used in this study were Completely Randomized Design with 4 treatments and 4 replications. The first treatment was S0 (wheat flour and coconut flour 100:0), the second treatment was S1 (ratio wheat flour and coconut flour 90:10), the third treatment was S2 (ratio wheat treatment and coconut flour 80:20), and the fourth treatment S3 ( ratio wheat flour and coconut flour 70:30). The data obtained was analyzed by statistic using Analysis of Variance (ANOVA) and then continue using Duncan’s New Multiple Range Test (DNMRT) at level 5%. The results of this research show that coconut flour significantly affected the moisture, protein and fiber contents, intactness, rehydration time, and sensory test. The best treatment was S1 (ratio wheat flour and coconut flour 90:10) which meet the dry noodle standart (SNI No. 01-2974-1996). Keywords: Dry noodle and coconut flour.